Advantages of taguchi method compared to response surface methodology for achieving the best surface finish in wire electrical discharge machining (WEDM) / Ananta Venkata Uday Kiran Kandala, Darius Gnanaraj Solomon and Joseph Jeyapaul Arulraj - Uday Kiran Kandala, Ananta Venkata; Solomon, Darius Gnanaraj; Arulraj, Joseph Jeyapaul (Universiti Teknologi MARA, 2022)
Design of Experiments is a method to predict the optimum conditions of a process to reduce the time and number of experiments to be conducted with limited resources. In this paper, a comparative work on design and analysis of experiments between Taguchi method and response surface methodology is carried out in predicting the set of optimal conditions for obtaining the best surface roughness of commercially pure titanium powder metallurgy component using wire electrical discharge machining process. With surface roughness of the Titanium as the response and pulse on time, pulse off time, and sintering temperature of the wire electrical discharge machining process as the affecting factors, the optimum conditions for the surface roughness of the material have been predicted and analysed. Analysis of variance is used to identify the significant factors affecting the system. Both methods gave the same results and the Taguchi approach requires less number of experiments compared to response surface methodology and the predicted surface roughness of the components with the Taguchi method is 2.4 μm, whereas it is between 2.41-3.04 μm with the Response Surface Methodology. The factor Pulse on Time (N) shows a significant effect on the response of the system.